Resilience monitor for informal caregivers for people with dementia (REMIND): Digital monitoring of informal caregivers' well‐being to prevent crises. (7th December 2020) - Oostra, Dorien L.; Nieuwboer, Minke S.; Rikkert, Marcel G.M. Olde; Perry, Marieke
Abstract: Background: The number of people with dementia living at home is likely to increase, resulting in a growing societal dependency on informal care. Informal caregiving causes a considerable burden on caregivers' wellbeing, both physical and mental. A decrease in caregivers' wellbeing is often a direct reason for crisis admission of the person with dementia. Close monitoring of wellbeing and resilience of caregivers followed by early intervening by case managers may prevent crisis. Our aim is to develop a user‐friendly digital monitor to assess wellbeing and resilience of caregivers to enable case managers to provide timely support and prevent crises. Method: A human centered design method was used. To identify wishes and needs, develop ideas for the monitor and test first visual prototypes, focus groups with end users and experts in the field of primary dementia care took place. End users were informal caregivers and professionals from different disciplines. Experts were researchers, clinicians, innovation experts and application designers. The 3‐month pilot study will include caregivers and case managers and consists of monitoring wellbeing and resilience weekly by a set of questions. Intervention delivery and acceptability will be assessed together with changes in number of crisis and caregiver's perseverance time. Result: Three focus groups with end user and multiple expert sessions took place. Wishes, needs and functionalities were identified during the first two focus group meetings. To detect deterioration of caregivers' wellbeing earlier, an application connected to a dashboard with an alert system for case managers is desired. To assess wellbeing, questions were reviewed during the third meeting covering the topics: social support, reciprocity, burden/competence, mood, own activities, small crises, person with dementia. Caregivers indicated they want to fill in approximately seven questions per week. Additionally, concept screens of the application and dashboard were discussed. Preliminary results of the pilot study will include adherence, user satisfaction and usability. Conclusion: This methodological approach will result in a product that best meets the needs and wishes of caregivers and case managers in order to prevent crises. The pilot study will provide insight into the possible effectiveness and usefulness of this product in practice.